Umbaúba arqueológica: entendendo um passado por trás do município - Nascimento, Marcel Raely Fontes Gonçalves (2014)
In wanting to understand the past of a society, we realized that the archaeological heritage attached to it, arises from the sum of different cultures that one day have lived in a particular region. However, the mere notion of the existence of this evidence, sometimes it is not enough to create an identity link between the past of a place and the current population that is what brings us to the city of Umbaúba - SE and its real lack of knowledge about the history its territory. Aiming to enhance the cultural heritage forgotten by the community, this research proposes to prospect the umbaubense territory, in order to identify sites of archaeological potential, until then, unknown by other archaeology professionals, considering the still little archaeological initiative in Sergipe. Making use of popular knowledge and the sparse documentation that refers to this municipality, we make use of a non-interventional and unsystematic prospection, which identified sites that had contributed to its importance and distinct occupations that occurred over time. Among them are: the Boa Hora Farm, with traces of a lithic pre-colonial site (polishing marks and/or sharpening tools amidst the rocks from Itamirim River), as well as ruins of the old sugar Mill Boa Hora and aqueducts that helped in its operation during the nineteenth century; the residence of the antique Campinhos Farm possibly related contexts of the nineteenth century; and the Pedra do Gentio, a cave described once, as indigenous shelter and another one used for rituals of African culture. From this, we have confirmed the municipal archaeological potential with a satisfactory outcome, although the diagnosis of the sites occurred only in a superficial way, conducting studies and fitting them for a period ahead.